Les trajectoires archivées des experts de la modernisation rurale alpine (XIXe-XXe siècles) - Sylvain Brunier; Nicolas Krautberger (Temporalités)
The purpose of this contribution is to suggest a historian’s way of dealing with individual careers and social context in the past. The main historical background is rooted in prosopographic studies that arrived from the United-States in the mid-1970s. We focus on social groups, using the comparative method to grasp their social characteristics. After a theoretical detour through Paul Ricœur’s historiography and Jean-Claude Passeron’s survey process, we present possible relational databases, not restricted to breaking historical sources down into series of biographical events. Fieldwork concerned a specific social group bringing together individuals who figure as experts of modernization in the rural Alpine world. Both politics of mountain reforestation at the end of 19th century, and of farm reconstruction after World War II produced many surveys, thanks to which experts’ trajectories, rather than being predetermined careers, can be reconstituted.